Effect Of Gasohol Blends On A Four Cylinder, Port Fuel Injection Engine Performance - Amirruddin, Abdul Kadir (2009)

(untitled)
This paper investigates the effect of using unleaded gasoline–ethanol blends on SI engine performance. A four stroke, four cylinder SI engine (type FORD, 16 V ZETEC) was used for conducting this study. Performance tests were conducted for equivalence air fuel ratio, fuel consumption, volumetric efficiency, brake thermal efficiency, brake power, engine torque and brake specific fuel consumption, using unleaded gasoline–ethanol blends with 50% and 100% throttle opening position and variable engine speed ranging from 1000 to 3000 rpm.The results showed that blending unleaded gasoline with ethanol increases the brake power, torque, volumetric,fuel consumption and brake specific fuel consumption. The addition of ethanol between 0-100 percent to the unleaded gasoline is achieved in the experiments without any problems during engine operation